2020
DOI: 10.3390/cells9102333
|View full text |Cite
|
Sign up to set email alerts
|

Tafazzin Mutation Affecting Cardiolipin Leads to Increased Mitochondrial Superoxide Anions and Mitophagy Inhibition in Barth Syndrome

Abstract: Tafazzin is a phospholipid transacylase that catalyzes the remodeling of cardiolipin, a mitochondrial phospholipid required for oxidative phosphorylation. Mutations of the tafazzin gene cause Barth syndrome, which is characterized by mitochondrial dysfunction and dilated cardiomyopathy, leading to premature death. However, the molecular mechanisms underlying the cause of mitochondrial dysfunction in Barth syndrome remain poorly understood. We again highlight the fact that the tafazzin deficiency is also linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 95 publications
(122 reference statements)
1
12
0
Order By: Relevance
“…Indeed, abnormalities of PE and PC lipid species have been reported in heart and skeletal muscle of BTHS patients, 39 as well as a specific depletion of plasmenylcholines in the heart of Taz ‐deficient mice 40 and human lymphoblast cells 41 . On the other hand, the same PL classes were demonstrated to not be altered in tafazzin deficient cell culture 42 and drosophila 43 models.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, abnormalities of PE and PC lipid species have been reported in heart and skeletal muscle of BTHS patients, 39 as well as a specific depletion of plasmenylcholines in the heart of Taz ‐deficient mice 40 and human lymphoblast cells 41 . On the other hand, the same PL classes were demonstrated to not be altered in tafazzin deficient cell culture 42 and drosophila 43 models.…”
Section: Discussionmentioning
confidence: 98%
“…187,188 Interestingly, a particular defect in the processing of LC3 was recently identified in a cell model of Barth syndrome. 189 Consistent with this, studies in tafazzin deficient cell models have revealed defective biogenesis of mitophagosomes. 190…”
Section: The Many Roles Of Cardiolipin In Stress Responsementioning
confidence: 61%
“…Also the adaptor molecule LC3 and functionally similar adaptor molecules, which label mitochondria for their degradation by mitophagy, have a high affinity for CL 187,188 . Interestingly, a particular defect in the processing of LC3 was recently identified in a cell model of Barth syndrome 189 . Consistent with this, studies in tafazzin deficient cell models have revealed defective biogenesis of mitophagosomes 190 …”
Section: The Many Roles Of Cardiolipin In Stress Responsementioning
confidence: 78%
“…The mitochondrial III 2 IV 2 supercomplex forms the terminal part of the electron transport chain and is essential for maintaining mitochondrial membrane potential and ATP synthesis (Schagger and Pfeiffer, 2000). In crd1Δ yeast, the III 2 IV 2 supercomplex is less stable than in wildtype cells, suggesting that CL is critical for mitochondrial homeostasis and bioenergetics (Pfeiffer et al, 2003;Mileykovskaya et al, 2005;Zhang et al, 2005;Claypool et al, 2008;Bottinger et al, 2012;Bazan et al, 2013;Peyta et al, 2016;Petit et al, 2020). A deficiency in CL remodeling is also associated with reduced bioenergetics (Brandner et al, 2005;Li et al, 2007).…”
Section: And Bioenergeticsmentioning
confidence: 99%
“…BTHS patients relative to non-BTHS control cells. More recently, Petit et al (2020) showed that shRNA-mediated Taz knockdown in HeLa cells results in decreased ATP synthase activity and overall ATP level, with a concomitant decrease in maximal respiratory capacity and an increase in basal oxygen consumption. Similarly, Dudek et al (2013Dudek et al ( , 2016 showed reduced respiratory complex formation in cardiac tissue isolated from the BTHS mouse model and increased basal oxygen consumption coupled with decreased maximal respiratory capacity in induced pluripotent stem cells (iPSCs) derived from BTHS patients.…”
Section: And Bioenergeticsmentioning
confidence: 99%